Makna Simbolik Tradisi A’barumbung Dalam Prosesi Pernikahan Adat Makassar Di Kecamatan Pallangga Kabupaten Gowa: The Symbolic Meaning of the A'barumbung Tradition in the Makassar Traditional Wedding Procession in Pallangga District, Gowa Regency - Apriaulia, Nur Reski; Hajrah, Hajrah; Fitri, Sakinah (Journal Studies in Indonesian Language and Literature, 2025)
This study examines the icons, indexes, symbols of a tradition and aims to describe the symbolic form and reveal the symbolic meaning contained in the a’barumbung tradition in the Makassar traditional wedding procession in Pallangga Village, Pallangga District, Gowa Regency. This study uses a descriptive qualitative method using Charles Sander Pierce's semiotic analysis. The data for this study are in the form of icons, indexes, symbols contained in the a’barumbung tradition during the Makassar traditional wedding procession in Pallangga District, Gowa Regency, especially in Pallangga Village. The data source for this study is the a’barumbung procession and anrong bunting who have extensive knowledge about a’barumbung or the bride and groom who have performed a’barumbung. The data collection techniques used in this study are direct observation, interview techniques, and documentation techniques.The results of the research show that the icons in the a'barumbung procession are: 1) Leko' (leaf) means hope, the index in the a'barumbung procession: 2) A'barumbung (steam bath) means maintaining purity and cleansing, 3) Diromo' (wrapped) means purifying, protecting, making happy, the symbols in the a'barumbung process: 4) Uring (pan) means listening to advice, 5) Je'ne (water) means the source of human life, 6) Kadera (chair) means broad-minded, 7) Berasa' (rice) means developing well, 8) taibani (candle) means a lamp to provide light for life, 9) Golla eja (brown sugar) means giving happiness, 10) Kaluku (coconut) means a harmonious life, 11) Tappere' (mat) means mutual respect, 12) Lipa' bate' (batik sarong) means persistence, 13) Salimu' (blanket) means selfesteem, 14) Javanese Kanre (cake) means human nature.